CaMKII is a nodal signal for multiple programmed cell death pathways in heart. (February 2017) - Feng, Ning; Anderson, Mark E.
Abstract: Sustained Ca 2 + /calmodulin-dependent kinase II (CaMKII) activation plays a central role in the pathogenesis of a variety of cardiac diseases. Emerging evidence suggests CaMKII evoked programmed cell death, including apoptosis and necroptosis, is one of the key underlying mechanisms for the detrimental effect of sustained CaMKII activation. CaMKII integrates β-adrenergic, Gq coupled receptor, reactive oxygen species (ROS), hyperglycemia, and pro-death cytokine signaling to elicit myocardial apoptosis by intrinsic and extrinsic pathways. New evidence demonstrates CaMKII is also a key mediator of receptor interacting serine/threonine kinase 3 (RIP3)-induced myocardial necroptosis. The role of CaMKII in cell death is dependent upon subcellular localization and varies across isoforms and splice variants. While CaMKII is now an extensively validated nodal signal for promoting cardiac myocyte death, the upstream and downstream pathways and targets remain incompletely understood, demanding further investigation. Highlights: CaMKII is activated and contributes to cardiomyocyte death by β-adrenergic signaling, Gq protein coupled receptor signaling, ROS, intracellular Ca 2 +, and pro-death cytokines. CaMKII elicits cardiac myocyte apoptosis in both intrinsic and extrinsic apoptotic pathways. CaMKII is an essential mediator of RIP-induced myocardial necroptosis. Both Ca 2 + /calmodulin-dependent activation and oxidative activation of CaMKII play a critical role in programmed cell death.